Primary central nervous system lymphoma presenting with Parkinsonism as an initial manifestation: A case report and literature review - Okano, Rintaro (Mol Clin Oncol, 2021)
Primary central nervous system lymphoma (PCNSL) is a rare intracranial neoplasm in older adults. Tumor-associated parkinsonism (TAP) in PCNSL is extremely rare, and its clinical features are unclear. The present report describes the case of a 75-year-old man who presented with parkinsonism due to multiple hyperintense lesions in the thalamus and periventricular white matter as visualized by magnetic resonance imaging (MRI). Due to the rapid progression of parkinsonism and lesion enlargement, the patient underwent stereotaxic biopsy. Subsequently, his condition was diagnosed as TAP in PCNSL at 2 months after onset. The patient completely recovered after treatment and experienced no recurrence of TAP for 8 months. Although it is difficult to distinguish TAP from vascular parkinsonism (VP) at initial consultation, the early diagnosis of PCNSL is important for improving prognosis. In the case of rapidly progressing parkinsonism, one should suspect the possibility of TAP associated with early-stage PCNSL. Early treatment improves the chances of remission and decreases the possibility of recurrence.